Pengembangan Media Pembelajaran Berbentuk Video Prosedur Penggunaan Ayakan Bertingkat (Granule Sieve) untuk Pembelajaran Blended Learning - deny sutrisno; barmi hartesi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Blended Learning is learning that involves face-to-face and brave learning that requires teaching materials that can be accessed by the brave. The purpose of this study was to create a learning media based on video as a guide to the use of Granule sieves and also to find out the feedback from the video. Methods of developing learning media through computers: (1) analyzing student needs; (2) formulating goals; (3) formulating the ingredients; (4) developing evaluation instruments; (5) writing scripts and taking pictures; (6) taking feedback (N = 57). In addition to the six steps, a validation test is also carried out before the field trial. This study result was a video learning that could be used as teaching material in the form of learning videos using granule sieves.